PENGARUH DESAIN PESAN VIDEO INSTRUKSIONAL TERHADAP PERSEPSI PETANI TENTANG TRICHOKOMPOS - Febria Yatimatul Munawaroh; Riyanto Riyanto; Andi Warnaen (Jurusan Ilmu Komunikasi UTM, 2019)
ABSTRACTThis research was conducted in District of Babadan Regency of Ponorogo East Java Province, to 62 chilli farmers and cattle farmers selected by simple random sampling. The purpose of this research is to know the influence of video usage and video message packaging elements to farmer perception about Trichokompos production and usage. The research design is One-Shot Case Study, independent variable used is narration, material, picture, music, time, and text, while the dependent variable is farmer perception on making and using Trichokompos. Information gathering on this is obtained through a structured questionnaire. Influence of video packaging element was analyzed by multiple regression statistic test, while farmer perception toward Trichokompos was analyzed using class interval model. The results showed that the perception of farmers about the making and use of Trichokompos influenced by independent variables of 52.1%, and the influence of instructional video message design partially indicates that the narrative, material, image, music, and text variables significantly influence farmers’ and the use of Trichokompos. However, time variables do not significantly influence farmers’ perceptions. Meanwhile, the perception of farmers about the making and use of Trichokompos shows that as many as 36 respondents or 58.1% claimed to receive Trichokompos innovation and perceived that the making and use of Trichokompos characteristic of innovation in accordance with that required by farmers, have the advantage, easy to apply by farmers, and materials standard available.